Exploring coupled electromechanical nonlinearities for broadband energy harvesting from low-frequency rotational sources. (20th May 2019) - Fu, Hailing; Zhou, Shengxi; Yeatman, Eric M
Abstract: This paper presents a methodology to effectively harness low-frequency broadband rotational energy using coupled electromechanical nonlinearities. This design integrates bi-stability and a synchronized switch harvesting on inductor (SSHI) circuit into a frequency up-converting harvester (FRUCH). The bistable behavior enables improved output power due to the increased vibration amplitude under the same input plucking force. The SSHI circuit exhibits enhanced conversion capability, contributing higher electrical damping which is ideal for FRUCHs to alleviate output power fluctuation at high frequencies. To study the coupled nonlinear dynamics from both the mechanical (bi-stability) and electrical (SSHI) sides, a system-level theoretical model is, for the first time, established and numerically solved using Matlab/Simulink. System behaviors, which would not be able to obtain using circuit simulation methods, are studied for different operating frequencies and load resistances. To validate the theoretical analysis, this harvester was implemented and tested experimentally. A close match was obtained. From the experimental results, an enhanced output power (up to 525%), over a broad frequency range, was realized, compared to that of a harvester with neither bi-stability nor SSHI circuits.